Acetaminophen Reactive Intermediates Target Hepatic Thioredoxin Reductase - Jan, Yi-Hua (American Chemical Society, 2014)
[Image: see text] Acetaminophen (APAP) is metabolized in the liver to N-acetyl-p-benzoquinone imine (NAPQI), an electrophilic metabolite known to bind liver proteins resulting in hepatotoxicity. Mammalian thioredoxin reductase (TrxR) is a cellular antioxidant containing selenocysteine (Sec) in its C-terminal redox center, a highly accessible target for electrophilic modification. In the present study, we determined if NAPQI targets TrxR. Hepatotoxicity induced by APAP treatment of mice (300 mg/kg, i.p.) was associated with a marked inhibition of both cytosolic TrxR1 and mitochondrial TrxR2 activity. Maximal inhibition was detected at 1 and 6 h post-APAP for TrxR1 and TrxR2, respectively. In purified rat liver TrxR1, enzyme inactivation was correlated with the metabolic activation of APAP by cytochrome P450, indicating that enzyme inhibition was due to APAP-reactive metabolites. NAPQI was also found to inhibit TrxR1. NADPH-reduced TrxR1 was significantly more sensitive to NAPQI (IC(50) = 0.023 μM) than the oxidized enzyme (IC(50) = 1.0 μM) or a human TrxR1 Sec498Cys mutant enzyme (IC(50) = 17 μM), indicating that cysteine and selenocysteine residues in the redox motifs of TrxR are critical for enzyme inactivation. This is supported by our findings that alkylation of reduced TrxR with biotin-conjugated iodoacetamide, which selectively reacts with selenol or thiol groups on proteins, was inhibited by NAPQI. LC-MS/MS analysis confirmed that NAPQI modified cysteine 59, cysteine 497, and selenocysteine 498 residues in the redox centers of TrxR, resulting in enzyme inhibition. In addition to disulfide reduction, TrxR is also known to mediate chemical redox cycling. We found that menadione redox cycling by TrxR was markedly less sensitive to NAPQI than disulfide reduction, suggesting that TrxR mediates these reactions via distinct mechanisms. These data demonstrate that APAP-reactive metabolites target TrxR, suggesting an additional mechanism by which APAP induces oxidative stress and hepatotoxicity.